An Annotated Bibliography in Financial Therapy - Jennifer Mentzer; Sonya L Britt; Jentry Samuelson; Jared Herrera; Dorothy B Durband (Journal of Financial Therapy, 2010)
The following annotated bibliography contains a summary of articles and websites, as well as a list of books related to financial therapy. The resources were compiled through e-mail solicitation from members of the Financial Therapy Forum in November 2008. Members of the forum are marked with an asterisk.